Combination of fluoride and endosulfan induced teratogenicity and developmental toxicity in Swiss albino mice exposed during organogenesis. (September 2019) - Sharma, Anju; John, PJ; Bhatnagar, Pradeep
The present investigation was conducted to evaluate the teratogenic and developmental toxicity of fluoride and endosulfan alone and in combination in pregnant Swiss albino mice exposed during the organogenetic period (5–14 days) of gestation. Fluoride (25.1 mg/kg body weight in water) and endosulfan (1.8 mg/kg bw by oral intubation) when administered alone and in combination (fluoride 25.1 mg/kg bw + endosulfan 1.8 mg/kg bw) to pregnant mice caused significant teratogenic effects in developing fetuses. There was no maternal mortality but significant decreases in maternal weight gain and numbers of live fetuses and significant increases in numbers of fetal resorption were recorded in the treated groups. The fetal body weight and litter size also decreased significantly in all treated groups. No external malformations were observed in any of the fetuses. The percent of visceral and skeletal anomalies increased in the fetuses of all treated groups. The fetal malformations observed were internal hydrocephaly, microphthalmia, anophthalmia, pulmonary edema, subcutaneous edema, reduced ossification of skull bones, widened cranial sutures, rib anomalies (short, wavy, partially ossified, or absent ribs), and reduced ossification of phalanges. The occurrence of visceral and skeletal malformations was more severe in the combination group, suggesting additive interaction of fluoride and endosulfan in inducing developmental toxicity in Swiss albino mice.